PAIN, DEMENTIA, AND RECURRENT FALLS AMONG COMMUNITY-DWELLING OLDER ADULTS IN THE UNITED STATES. (11th November 2018) - Patel, K V; Gell, N M; Le, M; Turk, D C
Abstract: Accumulating evidence suggests that pain is a risk factor for falls. Considering that pain is more common in community-dwelling older adults with dementia, we investigated the effects of pain and dementia on falls risk. Data collected annually on 7, 601 community-dwelling Medicare beneficiaries aged ≥65 years who participated in the 2011–2015 National Health and Aging Trends Study were analyzed. Over the 4-year follow-up period, the cumulative incidence of recurrent falls was 28.5%. Relative to older adults without bothersome pain and dementia, the risk of recurrent falls was 86% higher in those with pain but without dementia (RR=1.86; 95% CI: 1.68–2.06), 147% higher in those without pain but who had dementia (RR=2.47; 95% CI: 2.02–3.01), and 292% higher in those with both pain and dementia (RR=3.92; 95% CI: 3.43–4.47), adjusting for demographic characteristics. Results suggest that fall prevention programs should integrate pain management strategies tailored to older adults with and without dementia.